Syekh Hasan Maksum as the Mufti of the Deli Sultanate in the Twentieth Century: His Biography, Scholarly Works, and Contributions to Islamic Education in East Sumatra - Fachri Rinaldi; Achiriah Achiriah (Local History & Heritage, 2026)
This article examines Syekh Hasan Maksum as the Mufti of the Deli Sultanate in the twentieth century, emphasizing his biography, scholarly works, and contributions to Islamic education in East Sumatra. Although widely recognized as a prominent Muslim scholar, his intellectual legacy has received limited scholarly attention. This study aims to analyze his life, works, and educational contributions within the socio-religious context of the Deli Sultanate. A qualitative biographical approach was employed by analyzing archival records, historical documents, manuscripts, and relevant literature to reconstruct the significant experiences that shaped his intellectual and institutional roles. The findings demonstrate that Syekh Hasan Maksum served not only as the Mufti of the Deli Sultanate but also as an influential Muslim intellectual whose scholarly works and educational activities advanced Islamic education in East Sumatra. His contributions illustrate the close relationship between religious authority, Islamic scholarship, and educational development during the twentieth century. This study contributes to Indonesian Islamic historiography by highlighting Syekh Hasan Maksum's intellectual legacy and enduring role in advancing Islamic education.